PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MENJELASKAN PENTINGNYA KEUTUHAN NKRI MELALUI TARI BAMBU BAGI SISWA KELAS V SD N 1 KEDUNGOMBO TAHUN 2018/2019 - Indria Hurip (Universitas PGRI Yogyakarta, 2020)
AbstractThe purpose of this study is to increase learning activities and outcomes explaining the importance of the integrity of the Unitary Republic of Indonesia through Bamboo Dance for Class V Students of SDN 1 Kedungombo in 2018 / 2019. This research is a Classroom Action Research (CAR). The subjects of this study were 13th grade students of SD Negeri I Kedungombo, Baturetno District. This research was conducted in 2 cycles where each cycle was held 2 meetings. The results of this study are 1) There is an increase in student learning activities after the learning process is implemented by applying the Bamboo Dance learning model to the material explaining the importance of the integrity of the Unitary Republic of Indonesia, in the fifth grade students of SD Negeri I Kedungombo in the 2018/2019 academic year from pre-cycle to second cycle until reaching 92.3% or 12 students actively learn with an average value of learning activeness of 87.7. 2) There was an increase in student learning outcomes after the learning process was implemented by applying the Bamboo Dance learning model to the material explaining the importance of the integrity of the Unitary Republic of Indonesia, in the fifth grade students of SD Negeri I Kedungombo in the academic year 2018/2019, reaching (100%). Or 13 students complete learning with an average of 87.3 or in either category (B).Keywords: Activities and learning outcomes, Bamboo Dance learning model.